A questão filosófica do suicídio em Albert Camus : a revolta enquanto resistência ao absurdo - Forneck, Jeferson (2022)
The present work seeks to intensify the knowledge about the writings of Albert Camus (1913-1960). The concepts developed by the author about the absurd, suicide and revolt are analyzed. From the present analysis, the historical context in which the author of The myth of Sisyphus finds himself is investigated. Camus is a writer of his time, concerned with the human condition of the 20th century. Through the following work, the contribution to the absurd reality is investigated in the author's essays and novels. In the first cycle of his thought, called the cycle of the absurd, the essay The myth of Sisyphus and the novel The Stranger stand out. In this period the author is in his intellectual youth, he highlights the absurdity and loneliness in the midst of existence. The second cycle of thought is highlighted by the works The rebel and The plague. In the second cycle of thought, the author moves from individual thinking to collective and engaged thinking about life. We can see a great approximation of Camus with literature. An analysis is established based on the concepts developed by the author, with emphasis on the contribution of his writings to the 20th century. Finally, it is possible to identify in Albert Camus an author of his time engaged with what oppresses the human being, in addiction to enabling a contribution related to a reading key for the 21st century